Censorship and ideological control over the press in the Kuibyshev region in the 1930-ies - V. S. Kukhorev (Вестник Самарского университета: История, педагогика, филология, 2025)
The article focuses on analyzing mechanisms of ideological control over print media in the Kuybyshev Region during the 1930-ies, based on archival materials from Fond R-2247 of the Central State Archive of Samara Oblast and a comparative analysis of CPSU(b) party directives and regional practices. The author demonstrates how the censorship system, formally regulated by Politburo decrees, encountered systemic challenges: a shortage of qualified personnel, high workloads on censors, and simplified procedures for approving materials for publication through oral instructions. Particular attention is devoted to the transformation of the training system for journalists and censors: short-term courses at the Obllit (Regional Department of Press Control), designed to strengthen ideological indoctrination, addressed personnel shortages but reduced the professional quality of editorial work. Archival document analysis reveals the role of Obllit officials as key arbiters of ideological control, simultaneously subjected to pressure from party committees and bureaucratic contradictions. The study emphasizes that the Soviet censorship system was not static: despite efforts toward total surveillance, its effectiveness depended on local conditions, personnel policies, and adaptation to socio-economic transformations. These findings refine perceptions of censorship as a mechanism not only of repression but also of dynamic administrative information management, opening avenues for further research into regional aspects of Soviet media policy